1977
DOI: 10.1094/phyto-67-576
|View full text |Cite
|
Sign up to set email alerts
|

Gamete-Seed Transmission of Alfalfa Mosaic Virus and Its Effect on Seed Germination and Yield in Alfalfa Plants

Abstract: LEAN. 1977. Gamete-seed transmission of alfalfa mosaic virus and its effect on seed germination and yield in alfalfa plants. Phytopathology 67: 576-579. The percentage of alfalfa mosaic virus (AMV)-infected conditions, there was a reduction of 30.8-34.6% in seeds was determined in the commercial production of seven germination and a reduction of 45.1-68.6% in yield of seed by different cultivars of alfalfa. Seed transmission of AMV AMV-infected alfalfa. No systemic infection from the ranged from 0.6 to 10.3%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 1 publication
2
15
1
1
Order By: Relevance
“…The high percentage of infection in plants grown from diseased seeds is consistent with values obtained in other studies, which demonstrated that the probability of plant infection through seed transmission (i.e. when infected seeds are used) is high, although not 100% (Hemmati & McLean, 1977;Johansen et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…The high percentage of infection in plants grown from diseased seeds is consistent with values obtained in other studies, which demonstrated that the probability of plant infection through seed transmission (i.e. when infected seeds are used) is high, although not 100% (Hemmati & McLean, 1977;Johansen et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported in the study of seed transmission of AMV, FROSHEISER (1974) and HEMMATI and MCLEAN (1977) demonstrated in crossing experiments that AMV was transmitted to the embryo through the ovules. Despite these observations, Wu-COXSON et al (1975), using conventional thin-section electron microscopy, were unable to find particles of AMV in the ovules of alfalfa.…”
Section: Discussionsupporting
confidence: 88%
“…FROSHEISER (1974) and HEMMATI and MCLEAN (1977) reported that alfalfa mosaic virus (AMV) was transmitted to alfalfa embrj-os through the ovules, but WILCOXSON ct al. (1975) were unable to find AMV particles in thin-sections of 50 ovules from infected alfalfa plants by conventional electron microscopy.…”
Section: Cytopathologie Von Reifen Ovarien Aus Salatpflanzen Die Mitmentioning
confidence: 99%
“…In a few instances, for example, in tulip color-adding virus, infection results in increased pigmentation in some areas of the petals (Matthews, 1991). Virus infection may reduce pollen production and decrease seed set, seed size, and germination (Hemmati and McLean, 1977) (Figure 4.3). The effects of virus infection on these nectar guides and on the behavior of honeybees do not appear to have been studied.…”
Section: Mosaic Patterns and Related Symptomsmentioning
confidence: 99%